Impact of Consumer Awareness on Bank Lending Services to the Buying Behavior of Millennials in Metro Manila, Philippines - Etpison, Marie Christine R.; Payumo, Patricia Mae L.; Songcuan, Fervi Chris Ramiro; Barrion, Maria Giselle Lyn L. (Faculty of Economics, State Islamic University of Maulana Malik Ibrahim Malang, 2023)
Personal financial knowledge can help financial management, resulting in financial problems and economic inequality. This research investigates the impact of millennials' awareness of bank lending services impacts their consumer buying behavior and their everyday lives. Furthermore, the study aims to assist the financial and marketing industry by analyzing empirical evidence from the millennial generation, enabling banks and financial institutions to customize their promotions and advertising. The research employed the correlational research method and structural equation model (SEM) to assess the structure of consumer buying behavior with its confounding variables, such as demographic factors and COVID-19 considerations, and the independent variable of consumer awareness. Moreover, to produce these kinds of inferences, a survey questionnaire was distributed to two hundred seventy-one respondents from the millennial generation (26 - 41 years old) to assess their awareness of financial lending products. The results indicate that internal (demographics) and external (pandemic) factors significantly influence millennials' level of awareness of bank lending services. However, only internal factors such as social class and employment status significantly impact millennials' buying behavior.